PERT Scheduling Reduces Project Time and Cost: Penjadwalan PERT Memperpendek Waktu dan Mengurangi Biaya Proyek - Rohmatdhoni, Syarif; Putra, Boy Isma (Indonesian Journal of Innovation Studies, 2025)
General Background Project scheduling plays a crucial role in ensuring time and cost efficiency in industrial operations. Specific Background In electrical installation projects, inaccurate planning often leads to delays and increased costs. Knowledge Gap However, optimization of project scheduling using probabilistic methods is still not fully applied in small-scale industrial projects. Aims This study aims to evaluate project scheduling using the Program Evaluation and Review Technique (PERT) to improve time and cost planning. Results The results indicate that project duration decreased from 222 minutes to 163 minutes, while project costs were reduced from Rp232,362 to Rp170,608, resulting in significant savings without compromising work quality. The probability of project completion reached 99%, indicating a high level of planning reliability. Novelty This study provides a quantitative application of PERT in electrical installation projects with measurable efficiency outcomes. Implications The findings support the use of PERT as a reliable tool for optimizing project scheduling and cost management in similar industrial contexts. Keywords: Project Scheduling, PERT Method, Time Optimization, Cost Reduction, Network Analysis Key Findings Highlights Shorter completion duration achieved through critical path restructuring Budget allocation decreased while maintaining work standards High completion probability indicates strong planning reliability